Efektivtias Model Pembelajaran Problem Based Learning (PBL) dengan Bantuan ZEP Quiz Terhadap Hasil Belajar Peserta Didik Kelas VII - Nurul Risma Widyawati; Sri Purwati; Ruqoyyah Nasution; Nelda Anasthasia Serena; Suparno Putera Makkadafi (PendIPA Journal of Science Education, 2026)
The problem of low student learning outcomes in science education is the driving force behind this study. This condition is caused by a teacher-driven learning process and the use of traditional teaching materials, which makes students tend to be passive and have difficulty understanding complex ideas. The purpose of this study is to disseminate the impact of the PBL learning paradigm on the learning outcomes of seventh-grade students at SMPN 1 Sangasanga using ZEP Quiz. This study used a non-equivalent control group design and a quasi-experimental quantitative methodology. The experimental and control classes, consisting of research participants, were selected through purposive sampling. Test instruments in the form of pretests and posttests were used to collect data, and descriptive and inferential statistics were used for analysis. The learning outcomes of the experimental group were significantly higher than those of the control group, according to the study findings. At a significance threshold of 0.05, the Independent Samples T-Test produced a t-count score (9.166) which was higher than the t-table (2.011) and was reinforced by a sig. (2-tailed) score of 0.000. This finding projects that students at SMPN 1 Sangsanga can grow their learning outcomes by using the PBL approach by using the ZEP Quiz.